Neuromanagement: Adaptasi Pendekatan Neurosaintifik Dalam Pengembangan Karyawan - Fajar Wirahadi Kuncoro; Mochammad Isa Anshori (Journal Of Business, Finance, and Economics (JBFE), 2023)
This study aims to describe the role of Neuromanagement in developing employee productivity. In this study, researchers analyze the role of Neuromanagement, and identify alternative strategies based on Neuromanagement that can be applied in the context of organization and employee development. Through the literature study method, researchers found that the application of Neuromanagement provides significant benefits. Employee development based on the principles of Neuromanagement has significant potential for optimizing employee productivity and boosting organizational performance, such as in decision making, increasing motivation, training effectiveness, and adapting to change. This research provides new insights and innovative solutions in employee development and performance management, and contributes to the academic literature in this field.